Bacterial and Archaeal Diversity in Sulfide-Bearing Waste Rock at Faro Mine Complex, Yukon Territory, Canada. Issue 6 (1st June 2020) - Pakostova, Eva; Johnson, D. Barrie; Bao, Zhongwen; MacKenzie, Peter M.; Ptacek, Carol J.; Blowes, David W.
Abstract: Acid mine/rock drainage (AMD/ARD) is generated by the microbially-accelerated oxidative dissolution of sulfide minerals in working and abandoned mine sites, and some natural environments. Iron-oxidizing microorganisms (IOM) regenerate the oxidant Fe 3+, while sulfur-oxidizing microorganisms (SOM) contribute to AMD/ARD by generating H2 SO4 via the oxidation of elemental S and reduced inorganic sulfur compounds. Bacterial and archaeal diversity in 34 samples of sulfide-bearing waste rock recovered from three boreholes at the Faro Mine Complex (Yukon Territory, Canada; Pb/Zn production from 1969 to 1998) was investigated using high-throughput amplicon sequencing of 16S rRNA genes. A majority of the borehole pore water samples had circum-neutral or mildly alkaline pH (6.3 − 8.7), while some had low pH (3.3 − 5.2). Mean relative abundance of prokaryotic SOM/IOM accounted for 3.4% of the total amplicons. The acidophilic genera Alicyclobacillus and Acidithiobacillus were the most abundant sulfur- and iron-metabolizing prokaryotes detected, followed by neutrophilic and moderately acidophilic (non-iron-oxidizing) SOM. Sulfate-reducing bacteria (SRB) were also detected, accounting for 0.6% of total reads. The presence of both acidophilic and neutrophilic prokaryotes catalyzing transformations of sulfur and iron in the same samples suggests development of microenvironments within the waste rock where dynamic biogeochemical transformations of these elements occur.